Benzoic acid-organocatalyzed ring-opening (co)polymerization (ORO(c)P) of l-lactide and ε-caprolactone under solvent-free conditions: from simplicity to recyclability. Issue 23 (9th November 2018) - Mezzasalma, Leila; De Winter, Julien; Taton, Daniel; Coulembier, Olivier
Abstract : The development of sustainable synthetic approaches to biodegradable and biocompatible polymeric materials represents a key challenge in polymer chemistry. Abstract : The development of sustainable synthetic approaches to biodegradable and biocompatible polymeric materials represents a key challenge in polymer chemistry. A novel solvent-free and organocatalyzed ring-opening ( co )polymerization (ORO( c )P) method utilizing benzoic acid(BA) as simple thermostable carboxylic acid-type catalyst is proposed to not only produce structurally well-defined aliphatic homopolyesters derived froml -lactide (l -LA) and ε-caprolactone (CL), but also and, unexpectedly, statistical copolyesters based on the two monomer units. RO( c )P reactions were conducted in bulk in a temperature range of 155–180 °C, in presence of alcohols as initiators. A triblock copolymer, namely, PLLA- b -PCL- b -PLLA, was also synthesized, attesting to the "controlled/living" character of this BA-OROP process. A bifunctional mechanism is proposed to operate, involving activation of both the monomer and the propagating hydroxyl by H-bonding. Very importantly, the BA organocatalyst could be readily recycled by simple sublimation and could be reused in further organocatalytic cycles.